β-decay studies for shape coexistence - Garrett, P. E. (Frontiers in Physics, 2024)
β decay has played a key role in studies of shape coexistence throughout the nuclear chart. This has been due mainly to the sensitivity in γ-ray and conversion electron spectroscopy that can be achieved following the population of excited states by β decay. In some regions, the spectroscopic studies using β decay have been the first to suggest the presence of shape coexistence; in others, they have reinforced the suggestion and provided important spectroscopic data. The present work reviews some of the key regions, with a prime focus on the neutron-rich side of the valley of stability, where β-decay measurements have played an important role.